Odpowiedź:
1) 4x + 3y = 9
-x + 5y = 2 I×4
4x + 3y = 9
-4x + 20y = 8 (dodajemy obustronnie)
23y = 17
y = [tex]\frac{17}{23}[/tex]
4x + 3([tex]\frac{17}{23}[/tex]) = 9
4x = 9 - [tex]\frac{51}{23}[/tex]
4x = [tex]\frac{207}{23}[/tex] - [tex]\frac{51}{23}[/tex]
4x = [tex]\frac{156}{23}[/tex]
x = [tex]\frac{156}{92}[/tex] = [tex]\frac{78}{46}[/tex] = [tex]\frac{39}{23}[/tex] = 1[tex]\frac{16}{23}[/tex]
2) x + 7y = 12 I×(-3)
3x - 5y = 10
-3x -21y = -36
3x + 5y = 10
-16y = -26
y = [tex]\frac{26}{16}[/tex] = [tex]\frac{13}{8}[/tex] = 1[tex]\frac{5}{8}[/tex]
x + 7([tex]\frac{13}{8}[/tex]) = 12
x = 12 - [tex]\frac{69}{8}[/tex]
x = [tex]\frac{96}{8}[/tex] - [tex]\frac{69}{8}[/tex] = [tex]\frac{27}{8}[/tex] = 3[tex]\frac{3}{8}[/tex]
3) 2x - y = 3 I×2
-4x + 2y = 7
4x - 2y = 6
-4x + 2y = 7
0 = 13
Równanie sprzeczne, brak rozwiązań